2018
DOI: 10.1111/jen.12571
|View full text |Cite
|
Sign up to set email alerts
|

Population development of Frankliniella occidentalis and Thrips hawaiiensis in constant and fluctuating temperatures

Abstract: Temperature fluctuations may influence the behaviour of insects. Frankliniella occidentalis and Thrips hawaiiensis are sympatric pests on flower and vegetable host plants in China. This study evaluated the influence of constant (23.0°C) and fluctuating temperatures (average of 23.0°C) on the population development of these two species. The results showed that both of these pests showed faster development and higher fecundity at a constant temperature than at fluctuating temperatures when fed on Rosa rugosa flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…The reproductive traits of insect populations are important indicators that can be used to determine the fitness consequences of fluctuating temperatures (Marshall & Sinclair, 2010). It has been reported that fluctuating temperature conditions negatively affect the fecundity and longevity of adults compared with optimal constant temperatures (Cao et al., 2019; Carroll & Quiring, 1993; Li et al., 2018). Our results showed that fluctuating temperatures (20–30°C) significantly restrained subsequent adult reproduction, resulting in a delay in adult oviposition and a decrease in lifetime fecundity, mating frequency, mating percentage and ovarian development grade in both populations.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive traits of insect populations are important indicators that can be used to determine the fitness consequences of fluctuating temperatures (Marshall & Sinclair, 2010). It has been reported that fluctuating temperature conditions negatively affect the fecundity and longevity of adults compared with optimal constant temperatures (Cao et al., 2019; Carroll & Quiring, 1993; Li et al., 2018). Our results showed that fluctuating temperatures (20–30°C) significantly restrained subsequent adult reproduction, resulting in a delay in adult oviposition and a decrease in lifetime fecundity, mating frequency, mating percentage and ovarian development grade in both populations.…”
Section: Discussionmentioning
confidence: 99%
“…The control of the rate of development, reproductive capacity and other growth distribution patterns of this destructive, invasive pest is particularly relevant. It was shown that fluctuations in temperature had significant effects on all these aspects, which, in turn, directly affected the distribution of F. occidentalis [ 24 , 28 , 29 , 30 , 31 ]. In this study, the main environmental variables influencing changes in the distribution of F. occidentalis were identified based on the results of the jack-knife test and the contribution rate of the climate variables calculated using the Maxent model.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 41 ] found that the nymph duration of Cyrtorhinus lividipennis was significantly reduced and the female adult stage was evidently prolonged after adults were fed on Tagetes erecta , Trida procumbens , Emilia sonchifolia , and Sesamum indicum flowers. Flower petals were used as the test materials to determine the effect on the development of thrips [ 23 , 24 ]; compared with these studies, we emphasize the role of single rose petal to a whole rose flower.…”
Section: Discussionmentioning
confidence: 99%
“…WFT, as a flower-inhabiting insect, feeds predominantly on flowers and prefers Rosa rugosa flowers [ 22 ]. Cao et al [ 23 , 24 ] also reported that WFT had a higher population on R. chinensis flowers than that on Gardenia jasminoides flowers. Previous studies have shown that WFT caused the most damage when roses were in bloom, as breakouts occurred during this period [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%